Implementasi Mesin Pemisah Kulit Ari Kedelai Kering Otomatis dan Perbaikan Manajemen untuk Meningkatkan Produktivitas UMKM Tempe Rohmat Tulungagung - Ridlwan, Ahmad Ajib; Wibowo, Theodorus Wiyanto; Jatiningsih, Oksiana; Widagdo, Andika Kuncoro (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2025)
Tempe Rohmat Tulungagung MSME, located in Rejosasri Village, Gondang District, Tulungagung Regency, faces several problems in production and management aspects. The purpose of this program is to improve the quality and quantity of tempeh production with a focus on soybean epidermis stripping, soybean cracking, and epidermis separation in a way that is more efficient than conventional methods as well as good management training. The PKM implementation method by the PKM team together with students is carried out in the following stages, namely situation analysis, observation, interviews and discussions with partners, formulating priority problems, determining activity methods, design of automatic dry soybean epidermis separator machine, procurement of tools and materials, machine manufacturing, machine test stage, handover and application of machines, training on machine operation and maintenance to partners, business management training, periodic monitoring and evaluation, and reporting on the implementation of PKM. Concrete solutions offered for priority problems include the procurement and application of the Automatic Ari Soybean Skin Separator Machine in the production aspect, and improvements in the management of Tempe Rohmat MSMEs. The results of this activity, this dry soybean epidermis separator machine has a capacity of 300 kg / hour, 15 times the production capacity of wet soybean epidermis separation manually through the mining process of ± 20 kg / hour. Training and assistance in improving management in partner tempe MSMEs has had an impact on improving the implementation of good management starting from financial management, production management, and marketing management by recording business financial flows in an orderly and good manner using a simple cash book.